Levels of people participation in community based forest management of the Dry Zone Area in Myanmar: A case study of Chaung U, Nyaung U and Taungdwingyi Townships - Hla Myo Aung (2017)
The objectives of the study are to determine levels of participation in community based forests of three different management regimes and to explore the influences of social, economical, institutional and forest resource factors on the levels of participation of user groups in the Dry Zone area of Myanmar. Three community forest user groups (CFUGs) of Nwegawe, Nyaunggyi and Thebyu villages represent different management projects operated by UNDP/ FAO, JICA and local people of self reliance program. The total members of the three CFUGs are 385 households, and are the population of the study. The sample size of 196 households was calculated by using Taro Yamane’s formula with 5% error, 95% confidence coefficient and 50% degree of variability. Distribution of samples among the three CFUGs is 119, 55 and 22 for Nwegawe, Nyaunggyi and Thebyu villages, respectively. Questionnaire survey was conducted and head of household who was also members of three user groups were interviewed. Stepwise Multiple Regression Analysis was used to analyze the relationship between levels of participation and social, economical, institutional and forest resource factors. In-depth interview with 15 key informants was carried out to gain more details on levels of participation. The results of Stepwise Multiple Regression Analysis revealed a score of 4.227 (high level of participation) for the Thebyu project, 3.163 (moderate level of participation) for the Nyaunggyi project and 2.487 (low level of participation) for the Nwegawe project. Findings showed that level of education, forest income, attendance of meeting, labor sharing and collection of fodder and grass and amount of fuelwood collection positively and significantly influenced levels of participation in the three projects with the statistical significance at 0.05. From the study it was concluded that apart from the Thebyu project (self reliance program), levels of participation in community forest plantation in the Nwegawe and Nyaunggyi projects were low and moderate, respectively and those levels suggested the failure after termination of the projects. The findings of the research can be used for further revision of the Community Forest Instruction-1995 and enhancement of community involvement in forest management in the Dry Zone area of Myanmar.